Grid and Services Evolution - Yahyapour, Ramin; Talia, Domenico; Meyer, Norbert; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Grids are a crucial enabling technology for scientific and industrial development. Grid and Services Evolution, the 11th edited volume of the CoreGRID series, was based on The CoreGRID Middleware Workshop, held in Barcelona, Spain , June 5-6, 2008. Grid and Services Evolution provides a bridge between the application community and the developers of middleware services, especially in terms of parallel computing. This edited volume brings together a critical mass of well-established researchers worldwide, from forty-two institutions active in the fields of distributed systems and middleware, programming models, algorithms, tools and environments. Grid and Services Evolution is designed for a professional audience composed of researchers and practitioners within the Grid community industry. This volume is also suitable for advanced-level students in computer science. .
A Java Task Execution Manager for Commodity Grids -- Evaluation of Custom vs Commodity Technology-based Storage Elements. -- A Model of Non Functional Properties for Grid Resources -- Grid Checkpointing Service -- Extending GWorkflowDL: a Multi-Purpose Language for Workflow Enactment. -- Workflow Monitoring and Analysis Tool for ASKALON -- Using gLite to Implement a Secure ICGrid -- Grid-Based Workflow Management -- Fault Detection, Prevention and Recovery in Current Grid Workflow Systems -- Towards Self-adaptable Monitoring Framework for Self-healing -- Performance Monitoring of GRID superscalar: Summing up -- Authorizing Grid Resource Access and Consumption -- Graphical Tool for the Management of DIET GridRPC Middleware. -- An Efficient Protocol for Reserving Multiple Grid Resources in Advance. -- Scalable Concurrency Control in a Dynamic Membership -- Improving the Peer-to-Peer Ring for Building Fault-Tolerant Grids.
Keywords: Computer science; Computer organization; Microprocessors; Computer communication systems; Computer Science; Computer Communication Networks; Processor Architectures; Computer Systems Organization and Communication Networks; Electronic books